Peningkatan Pemasaran Produk Usaha Mikro Kecil Menengah Susu Pasteurisasi Melalui Legalitas Usaha dan Promosi Digital - Chania Ratu Iriana Putri; Dewi Maharani; Izza Syarifah Umamah; Nabila Rahmadina Octavyani (Jurnal Pemberdayaan Masyarakat, 2025)
MSMEs or Micro, Small and Medium Enterprises are one of the business units that have contributed to economic growth and have proven to minimize economic inequality, especially at the lower middle class level. One of the MSMEs in Jabung Village, Kemantren District, Malang Regency is MJP or Muncul Jaya Pasteurization. These MSMEs produce pasteurized milk with good properties for health. However, there are several obstacles that prevent this product from entering the market widely, namely the absence of an NIB or business identification number and the lack of digital promotion so that the marketing of this product is only limited. Based on this, this service was carried out to increase understanding of the knowledge of market requirements using NIB, as well as how to manage product marketing through digital media and label branding. The results of this service are increased knowledge of producers regarding marketing requirements through the NIB scheme and digital marketing media, the issuance of NIB documents as an initial requirement for making PIRT numbers or Household Industry Food and the inclusion of NIB numbers on product labels and increased product consumers after marketing through digital marketing methods.